Sense of Belonging and Lecturers’ Work Enthusiasm in the Campus Environment Context - Lubis, Indah Sari Liza; Setha, Donny (Journal of Educational, Health and Community Psychology, 2025)
This study examined the influence of campus facilities and environmental quality on lecturers’ work enthusiasm, with sense of belonging as a mediating variable. A quantitative cross-sectional survey was conducted among 74 lecturers at Universitas Tjut Nyak Dhien Medan. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Measurement items showed strong validity, with factor loadings between 0.802 and 0.876. Results revealed that campus facilities significantly affect both work enthusiasm (t= 3.187) and sense of belonging (t= 4.211). Environmental quality also exerts a significant effect on sense of belonging (t= 5.025) and work enthusiasm (t= 5.335). Moreover, sense of belonging positively influences work enthusiasm (t= 4.271), confirming its mediating role. The findings extend Resource-Based View, AMO framework, and Social Exchange Theory in the Indonesian higher education context. Practically, they suggest universities should enhance facilities, improve work environments, and foster belonging to strengthen lecturers’ enthusiast.